Application of “Internet +” continuous emotion management training in patients with depression - Yanping Zhang; Jiaxin Wang; Linlin Qiao; Yating Li; Runing Hou; Xiaojing Gu; Jingyuan Zhao; Fang Yan (Frontiers in Psychiatry)
ObjectiveExplore the application effects of “Internet +” continuous emotional management training in depression patients and analyze the feasibility of innovative rehabilitation training methods.MethodsConveniently selected 100 discharged patients meeting the diagnostic criteria for depression from the Second Affiliated Hospital of Xinxiang Medical University between August 2022 and January 2023 as study subjects. They were divided into an intervention group and a control group according to their discharge time, with 50 patients in each group. The control group received routine monthly telephone follow-ups and “Internet +” health popularization. The intervention group received “Internet +” continuous emotional management training in addition to the control group’s protocol. Before and after the intervention, the Hamilton Depression Rating Scale (HAMD), the Chinese version of the Cognitive Emotion Regulation Questionnaire (CERQ-C), and the Social Adaptation Function Evaluation Scale (SAFE) were used to compare the differences in depression relief, cognitive emotion regulation levels, and social functions between the two groups.ResultsTwo patients in the control group and three patients in the intervention group were lost to follow-up during the intervention, Ultimately, 48 patients in the control group and 47 patients in the intervention group completed the study. Before the intervention, there were no statistically significant differences between the two groups in HAMD scores, CERQ-C subscale scores, and SAFE scores (P < 0.05). After the intervention, the intervention group had significantly lower HAMD and SAFE scores compared to the control group (P < 0.05). In the CERQ-C questionnaire, the intervention group scored lower in self-blame, rumination, catastrophizing, and blaming others but higher in acceptance, positive refocusing, refocusing on planning, positive reappraisal, and putting into perspective compared to the control group, with statistically significant differences (P < 0.05).Conclusion“Internet +” continuity emotion management training can reduce the severity of depression in post-discharge patients and enhance their emotional management and social adaptability. This approach is feasible in clinical practice.